Cultural Pluralism and Islamic Legal Ethics: Reimagining Family Law for Interreligious Marriages in Banyumas - Muchimah; Komalasari, Nunung; Fadhil , Rahmatul; Milki Aan; Humaira Ahmad (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This research explores the encounter between cultural pluralism and Islamic legal ethics within the context of interreligious marriage in Banyumas, Indonesia. Although there are formal legal and religious restrictions toward interfaith marriage, many couples in Banyumas continue to perform their respective religious rituals within shared domestic life. By utilizing a socio-legal approach and qualitative methods which included in-depth interviews, participant observation, as well as document analysis, this study focused attention on significant ritual moments such as marriage ceremonies, birth traditions, and death rites, because those moments constituted crucial arenas where religious norms, legal expectations, and cultural values intersected and were tangibly negotiated. The findings of the research indicate that cultural values such as rukun (harmony), tepa selira (mutual consideration), and cablaka (openness) play a central role in enabling peaceful coexistence and symbolic negotiation within those households. Rather than adhering rigidly to legal formalism, interreligious families rely upon adaptive ethical reasoning which is rooted in Islamic principles, particularly maqasid al-shari‘ah (the higher objectives of Islamic law). This research offers a rearticulated framework for family law which is inclusive, contextual, and responsive toward the realities of life within plural society. This study also proposes a dynamic model of Islamic legal ethics which integrates legal pluralism, human dignity, and protection of fundamental rights, as well as offers new pathways for legal reform within the context of multicultural society with Muslim majority.